Gamification's Contribution to Creativity Enhancement: A Bibliometric Analysis of Empirical and Theoretical Studies in the Last Decade - Krisanti, Galuh Dwi; Damarsha, Adrian Bagas; Yuliatin, Elisa Dwi; Hidaayatullaah, Hasan Nuurul; Suprapto*, Nadi; Saphira, Hanandita Veda (Jurnal Pendidikan Sains Indonesia, 2025)
Many studies have been conducted on creative thinking and gamification separately, but there is still a gap in the literature that examines the relationship between these two concepts comprehensively in an educational context. This research was conducted with the aim of providing a more holistic understanding of the trending topics between gamification and creative thinking in empirical and theoretical studies, analysing the contribution of each author using the Scopus database through bibliometric analysis with the VOSviewer application. Based on bibliometric analysis, several conclusions are obtained that the results of the metadata obtained show a trend of writing that is growing significantly from 2013 to 2023. In the author collaboration network, it can be seen on the map that there are 8 clusters with the number of author items each totalling 1 item where each author has published 2 documents. From the results of the analysis, the topic of gamification for creativity is still needed and needs to be improved. United States contributes to publishing documents on the topic of gamification for creativity. For the form of publication, most documents are published in the form of articles. So for the right solution in improving CTS can be done by using gamification learning